Analisis Solar Tracking pada Pembangkit Listrik Tenaga Surya Sebagai Sumber Tenaga Lampu Jalan: Penelitian - Devanta Abraham Tarigan; Alexander Sebayang; Efrata Tarigan; Liwat Tarigan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The utilization of solar energy in Indonesia is still very low despite its huge potential. One of the causes of the low efficiency of solar panels is static installation that does not follow the direction of sunlight. To overcome this, an automatic solar tracker system was designed and built on a 20WP Solar Power Plant (PLTS) as a source of energy for street lights. This research uses a design and experiment method, which involves the development of an ESP32 microcontroller-based system, equipped with a GY-271 compass sensor, INA219 current and voltage sensors, and a DS3231 RTC module. A servo motor is used to automatically adjust the panel's position to follow the direction of the sun. This system is also equipped with an LM2596 Step-Down regulator and is programmed using the Arduino IDE, and can send real-time monitoring data via Wi-Fi to a smartphone. The experimental results show that the solar tracker system is able to increase electrical power up to more than a static panel at the same test time. The panel follows the movement of the sun from east to west, resulting in higher power efficiency throughout the day. Comparison of data between the tracker system and the panel still shows a significant difference in power at each hour of measurement. Testing has begun and has yielded an average power increase of 20.41% compared to static solar panels.